2018
DOI: 10.1186/s12992-018-0400-7
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of a mobile phone supported family-centred ADL intervention, F@ce™, after stroke in Uganda

Abstract: BackgroundThere is a lack of evidence-based health services to reduce the impact of stroke in low-income countries at a personal, family or community level.The aim was to evaluate the feasibility of: i) a mobile phone supported family-centred intervention (F@ce™), and ii) the study design for evaluating the effects of the intervention on the perceived impact of stroke; perceived participation in everyday life; and self-efficacy in everyday activities amongst persons with stroke and their families in Uganda.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(101 citation statements)
references
References 47 publications
(55 reference statements)
4
74
0
1
Order By: Relevance
“…Areas that supported feasibility were as follows: findings related to acceptability indicated that the intervention, which included individual support for two months, was perceived to be appropriate according to patients' needs. Similar results, concerning intervention duration, was found in a study using SMS reminders in stroke rehabilitation [27]. Regarding the area of demand, patients expressed interest and their actual use of RemindMe showed that it was used to support activities in everyday life.…”
Section: Discussionsupporting
confidence: 81%
“…Areas that supported feasibility were as follows: findings related to acceptability indicated that the intervention, which included individual support for two months, was perceived to be appropriate according to patients' needs. Similar results, concerning intervention duration, was found in a study using SMS reminders in stroke rehabilitation [27]. Regarding the area of demand, patients expressed interest and their actual use of RemindMe showed that it was used to support activities in everyday life.…”
Section: Discussionsupporting
confidence: 81%
“…This study was a sub-study of a larger overall clinical study (F@ce), described elsewhere [28]. The study was a collaborative project between Karolinska Institutet (KI) in Stockholm (Division of Occupational Therapy), Sweden; Stockholm University, Sweden (SMS-system development and related services); and Uganda Allied Health Examinations Board (coordination of local OTs).…”
Section: Methodsmentioning
confidence: 99%
“…F@ce stands for Face-to-face (F) with a collaboration between the therapist and a client during all the different phases, including Assessment (@), Collaboration (C) and Evaluation (E). The F@ce™ intervention integrates the principles of client-centred practice with goal setting involving daily occupations that the person need and want to do in everyday life during the entire rehabilitation process and has in a feasibility study been found to improve primary outcomes (performance and satisfaction of valued daily activities in everyday life assessed using the Canadian Occupational Performance Measure (COPM), as well as self-efficacy [28].…”
Section: Introductionmentioning
confidence: 99%
“…The process evaluation was carried out by two evaluators within the context of a research project in Uganda. The purpose of the main research project was to evaluate the feasibility of a model for mobile phone-supported and family-centred rehabilitation intervention to increase functioning in daily activities for persons living with the consequences of stroke, as well as participation in everyday life for persons with stroke and their family members [27].…”
Section: Methodsmentioning
confidence: 99%